APPLICATION OF INDONESIAN RULES IN THE REGULATION OF THE SUPREME COURT OF THE REPUBLIC OF INDONESIA - Aminulloh, Muhamad; Astriani, Anjar (DE'RECHTSSTAAT, 2023)
In making legal products, the use of written language that is in accordance with the Indonesian Standard Rules and General Guidelines for Indonesian Spelling requires accuracy in the framework of conformity in sentences contained in laws and regulations. This is done so that there is no misinterpretation of the message contained in the legal product. The phenomenon that occurs is that many legal experts in making legal products such as regulations, legislation, contracts, agreements, MoUs, and the like do not heed or even underestimate the rules in the Indonesian language. The method used in this study is a qualitative method, while the type of research used is content analysis, which means a model used to examine data documentation in the form of text, images, symbols, and so on. In making legal products, using written language that is in accordance with the "Indonesian Standard Rules of Procedure" and "General Guidelines for Indonesian Spelling" will minimize or even eliminate the risk of misinterpretation of the messages contained in these legal products in Indonesian in legislation in basically it is no different from other Indonesian languages, the difference lies only in terminology or the use of certain terms.